Challenges to the Development of Creative Economy SMEs in Banyumas Regency due to Social Distancing Policies During the COVID-19 Pandemic - Aziz Ahmad, Abdul; Sabiq, Ahmad; Rosyadi, Slamet; Kurniasih, Denok (KnE Social Sciences, 2023)
Using small and medium enterprises (SMEs) in the creative economy sector of Banyumas Regency, Indonesia, we map the activity of SMEs in the creative economy sector before the COVID-19 pandemic and conduct a descriptive analysis based on interviews with respondents of creative economy SMEs during the COVID-19 period in 2021. The results of this study shows the distribution of the potential for creative economic development in the Banyumas Regency area. From 2020 to 2021, the creative economy in the Banyumas area experienced shocks due to the impact of the COVID-19 pandemic. COVID-19 has reduced people’s purchasing power, directly impacting the decline in business turnover. To overcome the effects of social distancing or the implementation of community activities restriction policies, creative economy entrepreneurs in Banyumas developed new products, expanded marketing methods with online media, and created new businesses to capture economic opportunities in trending community activities. The creative economy SME actors in Banyumas appreciate the importance of government assistance to protect them from the impact of the COVID-19 pandemic. Keywords: creative economy, small and medium enterprises, social distancing policy, COVID-19